2007
DOI: 10.1016/j.tsf.2007.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Investigations in the initial build-up stages of polyelectrolyte multilayers by laser reflectometry and atomic force microscopy

Abstract: This work aims to investigate the initial build-up stages of polyelectrolyte multilayers formed by the successive deposition of the weakly charged Poly(Allyl amine, HCl), PAH and the strong acid Poly(Styrene Sulfonate), PSS, on silica at pH = 9. Two complementary tools were used: laser reflectometry to determine the step-by-step deposited weight of each polymer and Atomic Force Microscopy (AFM) to characterize the topography and measure the thickness of the film. The experiments show that the deposited weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 19 publications
(31 reference statements)
8
22
0
Order By: Relevance
“…This quasi plateau is attributed to the polymer film concentration. After the formation of coacervates between PSS and PAH on the substrate in the first layer, there are densification of the aggregates by diffusion of the PSS into the aggregates [11]. Similar results were found by Buron et al [21] for MAQUAT/PAA.…”
Section: Polymer Film Thicknesssupporting
confidence: 84%
See 4 more Smart Citations
“…This quasi plateau is attributed to the polymer film concentration. After the formation of coacervates between PSS and PAH on the substrate in the first layer, there are densification of the aggregates by diffusion of the PSS into the aggregates [11]. Similar results were found by Buron et al [21] for MAQUAT/PAA.…”
Section: Polymer Film Thicknesssupporting
confidence: 84%
“…However, this structure can be obtained by the conformation of the polymer during the adsorption. Indeed, in a previous paper [11], we have shown that the polyelectrolytes form PAH/PSS aggregates on the silica surface and that PAH can adsorb on the top of the aggregates and so coalesce to aggregates by the summits. In this process, cavities form between two aggregates and can be observed by FIB.…”
Section: Wafer With Adsorbed Polymer Filmmentioning
confidence: 87%
See 3 more Smart Citations